The Hubungan Konsumsi Junk Food dengan Gangguan Siklus Menstruasi pada Remaja Putri di SMK Ar Rahma Gempol, Kabupaten Pasuruan - Nurul Agustin (Rena Cipta Mandiri, 2026)
Background : Menstrual cycle disorders are conditions characterized by abnormal changes in the frequency, duration of menstruation, and the volume of menstrual blood. Data obtained from Riskesdas show that 13.7% of women in Indonesia aged 10–59 years experienced irregular menstrual cycles within the last year. These disorders can be influenced by various factors, one of which is the habit of consuming junk food. Objective : This study aimed to analyze the relationship between junk food consumption and menstrual cycle disorders among female adolescents at SMK Ar-Rahma in 2025. Methods: This study used a quantitative analytic method with a cross-sectional design. The research was conducted from August 30 to September 2025 with a total population of 143 adolescents. The sampling technique used purposive sampling, resulting in 59 respondents. Data collection in this study used an FFQ questionnaire and a checklist sheet. Data analysis was performed using the Chi-Square statistical test. Results : The results showed that most adolescents frequently consumed junk food, totaling 42 respondents (71.2%), and 51 respondents (86.4%) experienced menstrual cycle disorders. Bivariate analysis using the Chi-Square test (p = 0.003) indicated a significant relationship between junk food consumption and menstrual cycle disorders. Conclusions: Therefore, concrete efforts are needed through promotive, preventive, and educative activities, accompanied by the development of effective strategies to improve adolescent reproductive health through appropriate nutritional approaches.